School politics and innovative experiences in Italy (1861–2015) - Bellatalla, Luciana (Acta Paedagogica Vilnensia, 2016)
In my paper, I describe educational experiences carried out not in the name of political choices, but thanks to engaged educators or/and philanthropists. Official school politics have been dominated by conservatism and elitism, whereas educators and philanthropists tried different didactical ways, working out a different idea of a school. The core of the paper is to compare official political school-models and non-official models. At the end, two questions are raised: Why have these experiences not influenced political choices? Why have teachers, politicians and educational theorists not interacted?